Comparative toxicity of antifouling compounds on the development of sea urchin - Perina, Fernando Cesar [UNESP]; de Souza Abessa, Denis Moledo [UNESP]; Leaes Pinho, Grasiela Lopes; Fillmann, Gilberto (Springer, 2011)
In the present study, embryotoxicity experiments using the sea urchin Lytechinus variegatus were carried out to better clarify the ecotoxicological effects of tributyltin (TBT) and triphenyltin (TPT) (the recently banned antifouling agents), and Irgarol and Diuron (two of the new commonly used booster biocides). Organisms were individually examined to evaluate the intensity and type of effects on embryo-larval development, this procedure has not been commonly used, however it showed to be a potentially suitable approach for toxicity assessment. NOEC and LOEC were similar for compounds of same chemical class, and IC10 values were very close and showed overlapping of confidence intervals between TBT and TPT, and between Diuron and Irgarol. In addition, IC10 were similar to NOEC values. Regardless of this, the observed effects were different. Embryo development was interrupted at the gastrula and blastula stages at 1.25 and 2.5 mu g l(-1) of TBT, respectively, whereas pluteus stage was reached with the corresponding concentrations of TPT. Furthermore, embryos reached the prism and morula stages at 5 mu g l(-1) of TPT and TBT, respectively. The effects induced by Irgarol were also more pronounced than those caused by Diuron. Pluteus stage was always reached at any tested Diuron concentration, while embryogenesis was interrupted at blastula/gastrula stages at the highest concentrations of Irgarol. Therefore, this study proposes a complementary approach for interpreting embryo-larval responses that may be employed together with the traditional way of analysis. Consequently, this application leads to a more powerful ecotoxicological assessment tool focused on embryotoxicity.
Keywords: Antifouling; Aquatic pollutant; Assessment tool; Ecotoxicology; Embryo-larval response; Embryogenesis